Higher gut Bacteroidetes and Actinobacteria population in early pregnancy is associated with lower risk of gestational diabetes in the second trimester - Seyedeh Neda Mousavi; Navid Momeni; Hossein Chiti; Howra Mahmoodnasab; Mohammad Ahmadi; Siamak Heidarzadeh (BMC Pregnancy and Childbirth)
Abstract Background Despite the association between the gut dysbiosis and metabolic disorders, the main bacterial phylum in the first trimester of pregnancy that predisposes mothers to gestational diabetes mellitus (GDM) in the second trimester is not clear around the world. Materials and methods Three-hundred healthy women aged 18–40 years who were in the first trimester were participated in this cohort study and followed to the screening time for GDM diagnosis (in 24–28 weeks of pregnancy). Stool samples were gathered in the first trimester. GDM was diagnosed based on the International Association of Diabetes and Pregnancy Groups. In total, thirty mothers were diagnosed with GDM. Controls (N = 60) were selected from non-GDM participants matching to the GDM in terms of pre-pregnancy weight, weight gain, dietary intake and familial history of diabetes. The dominant phylum population was determined based on 16SrRNA gene expression. Results Mothers with lower Bacteroidetes and Actinobacteria population in the first trimester were more susceptible to GDM in the screening time (p < 0.001 and p < 0.001). The Firmicutes to Bacteroidetes ratio was significantly higher in mothers with GDM than the controls (p < 0.001). A significant negative correlation was observed between the gut Bacteroidetes (p < 0.001, p < 0.001, p < 0.001) and Actinobacteria (p = 0.004, p < 0.001, p = 0.02) population in the first trimester with the the serum FBS, 1 h-PG and 2 h-PG levels in the screening time. However, the gut Firmicutes to Bacteroidetes ratio (p = 0.003, p = 0.01) showed a significant positive correlation with serum FBS and 1 h-PG levels. Conclusions A higher Bacteroidetes and Actinobacteria population in the gut of mothers at the first trimester was associated with lower risk of GDM in the screening time. Higher Firmicutes to Bacteroidetes ratio in the gut of mothers was associated with fasting and 1-h glucose intolerance in the screening time.